2017
DOI: 10.1016/j.dnarep.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The NAD + precursor nicotinic acid improves genomic integrity in human peripheral blood mononuclear cells after X-irradiation

Abstract: NAD is an essential cofactor for enzymes catalyzing redox-reactions as well as an electron carrier in energy metabolism. Aside from this, NAD consuming enzymes like poly(ADP-ribose) polymerases and sirtuins are important regulators involved in chromatin-restructuring processes during repair and epigenetics/transcriptional adaption. In order to replenish cellular NAD levels after cleavage, synthesis starts from precursors such as nicotinamide, nicotinamide riboside or nicotinic acid to match the need for this e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 119 publications
0
11
0
1
Order By: Relevance
“…Because p53 is deacetylated by SIRT1 the Acp53/p53 ratio was used to assess the activity of SIRT1 (Chung et al 2015;Feng et al 2015;Kim et al 2016;Li et al 2015;Song et al 2015;Weidele et al 2017) and the results showed that exercise and NAM treatment as well as the combined effects of these increased the activity of SIRT1 in old muscle. In terms of exercise training this is similar to our earlier results (Koltai et al 2010(Koltai et al , 2012 however, the intensity of training was much less than that used in those studies.…”
Section: Discussionmentioning
confidence: 99%
“…Because p53 is deacetylated by SIRT1 the Acp53/p53 ratio was used to assess the activity of SIRT1 (Chung et al 2015;Feng et al 2015;Kim et al 2016;Li et al 2015;Song et al 2015;Weidele et al 2017) and the results showed that exercise and NAM treatment as well as the combined effects of these increased the activity of SIRT1 in old muscle. In terms of exercise training this is similar to our earlier results (Koltai et al 2010(Koltai et al , 2012 however, the intensity of training was much less than that used in those studies.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, elevated levels of NA have been shown to improve genomic integrity by reducing micronucleus frequency, and NA deficiency results in chromosomal instability (178)(179)(180)(181). Treatment with NA has been reported to delay carcinogenesis, enhance repair efficiency following cand X-irradiation in mouse melanoma cells and human PBMCs, and improved neuronal function following hypoxic insult (244,362). NA has also been shown to enhance endothelial protection by increasing endothelial levels of NADP + and GSH (114).…”
Section: Fig 11 Modulation Of Nad 1 and Nad-dependent Pathways By Cmentioning
confidence: 99%
“…Also based on our results showing an increased SIRT1 and PARP1 activity and inhibited p21 accumulation in m-HCD pups supplemented with niacin, we can suggest that niacin-derived NAD + only acts at the nuclear level. This assumption is nicely supported by a recent paper demonstrating that niacin supplementation efficiently promotes nuclear DNA repair in X-irradiated human peripheral blood cells via the enhancement of SIRT1 activity [ 40 ].…”
Section: Discussionmentioning
confidence: 71%